Efficacy of epidural steroid injection in management of lumbar disc lesion - Hussein A.E.A El-Ghait; Ahmed I Akar; Abdelazim A Hegazy; Mahmoud A.E.M El-Maadawy (Wolters Kluwer Medknow Publications, 2021)
Background and aim Low back pain and radiculopathy are the main annoying complaints in patients with degenerative disc diseases. Epidural steroid injection (ESI) has a role to reduce pain and improve disability by decreasing inflammatory process at the nerve root caused by herniated disc. This study was done to evaluate the efficacy of lumbar ESI regarding the improvement of pain and functional outcome. Patients and methods This study was a prospective randomized study on 30 patients, aged between 30 and 65 years with low back pain and lumbar radiculopathy secondary to lumbar disc prolapse with no absolute indication for surgery. The patients were treated by lumbar epidural injection of steroids. Patients were divided randomly into two groups: group 1 included 15 patients subjected to lumbar interlaminar ESI, and group 2 included 15 patients subjected to lumbar transforaminal ESI. Patients were evaluated using visual analog scale (VAS) score for pain and the Oswestry Disability Index (ODI) for functional capacity. They were followed up after 4 weeks, and clinical and functional outcomes were assessed using the same tools for evaluation. Results The mean VAS for the 30 patients improved by 58.33% (P<0.001), and the mean ODI for the 30 patients improved by 35.4% after 4 weeks following injection (P<0.001). In group 1, the mean VAS improved by 52% and the mean ODI improved by 31.13% after 4 weeks following injection (P<0.001). In group 2, the mean VAS improved by 64.66% and the mean ODI improved by 39.66% after 4 weeks following injection (P<0.001). We found that the mean improvement of VAS and ODI was more in group 2 than in group 1(P<0.026). Conclusion We found by the end of the study that the ESI is a safe and effective procedure in alleviating radicular pain and improvement of functional outcome, but the transforaminal approach gives better results than the interlaminar approach.